The impact of niche marketing strategies on marketing performance / Muhd Naim Razali - Razali, Muhd Naim (Faculty of Business and Management, 2008)
The purpose of this research is to know impact of niche marketing strategies on marketing performance, by finding the determinants that contributes to niche marketing strategies on marketing performance; to study the relationship between segmentation, targeting, differentiation and positioning on marketing performance, design and finally to provide some recommendation and suggestion for Ministry of Entrepreneur and Cooperative Development, Ministry of International Trade Industries to improve the effectiveness of SME product's marketing. It is found that some of the small and medium companies still cannot improve their marketing performance. As to solve their problem researcher suggest implementing niche marketing strategies to improve their marketing performance. Part of the reason is because the marketers not fully utilize marketing strategies to improve their marketing performance. In this paper, the researcher conducted a survey of company preferences. 100 respondents were selected among the companies listed in Small Medium Industries Development Corporation (SMIDEC). The respondents were asked to complete a questionnaire concerning their preferences on niches marketing strategies on marketing performance. The finding shows that only segmentation, targeting and differentiation give a positive effect to marketing performance.